A New Infrageneric Classification of Mucuna (Leguminosae-Papilionoideae): Supported by Morphology, Molecular Phylogeny and Biogeography - Moura, Tania Maria de; Wilmot-Dear, Melanie; Vatanparast, Mohammad; Fortuna-Perez, Ana Paula [UNESP]; Tozzi, Ana M. G. A.; Lewis, Gwilym P. (Amer Soc Plant Taxonomists, 2016)
The previous infrageneric classification of Mucuna (Leguminosae, Papilionoideae) recognized two subgenera, M. subg. Mucuna and M. subg. Stizolobium, but that classification is not supported fully by molecular phylogenetic analyses, which reveal three main clades in Mucuna (rather than the traditional two). A new taxon M. subg. Macrocarpa is proposed based on the results of a molecular phylogenetic analysis, supported by fruit characters and biogeography. Historically, the representatives of this new subgenus were considered as members of M. subg. Mucuna, but species of subgenus Macrocarpa differ from species of the other two subgenera by their longer ovaries containing a higher number of ovules and, consequently, longer pods containing more seeds, and by the different fruit length to width ratio. This study presents a new infrageneric classification of the genus Mucuna. The six species of M. subg. Macrocarpa are reviewed, and species descriptions, typifications (including five new lectotypes), a distribution map, and a species identification key are presented.
Keywords: Character evolution; cladistics; Fabaceae; new taxon; taxonomy